Representasi Daya Tarik Model Wanita Dalam Mengonstruksi Citra Merek dan Gaya Hidup Pada Iklan Kopi Kapal Api di Media Digital - Novita Sari; Eko Prasojo (CV Muara Edukasi, 2026)
The rapid growth of digital media has fundamentally transformed brand communication strategies, particularly in Indonesia's competitive coffee industry. This study examines how the attractiveness of female models is represented in Kapal Api's digital advertisements to construct brand image and lifestyle. Employing Roland Barthes' semiotic analysis, which encompasses denotation, connotation, and myth, this qualitative research analyzes five digital advertisements published between 2022 and 2025. These advertisements feature prominent female models, including Ariel Tatum, Nagita Slavina, Gege Elisa Joy Callista, and Maudy Ayunda. The findings reveal three distinct representational patterns. The first is autonomous aesthetic representation, which emphasizes creativity and cultural pride. The second is professional-intellectual representation, which highlights expertise and productivity. The third is social-relational representation, which focuses on family warmth and gender equality. These patterns function through the Source Attractiveness Model proposed by Ohanian and the Meaning Transfer Model introduced by McCracken. The models successfully transfer symbolic values, such as elegance, professionalism, warmth, and practicality, to the brand. This layered representation strategy effectively repositioned Kapal Api from a traditional masculine coffee brand to an inclusive and modern brand that appeals to urban women across various social roles. The study contributes theoretically by integrating semiotics with marketing theories and offers practical strategic insights for visual communication in digital branding